The effect of social media marketing activities on brand awareness, brand image and brand loyalty for the Netflix brand - Richardi Fariandi; Dorothea Wahyu Ariani (Junal Ilmu Manajemen, 2023)
This study aims to analyze how social media marketing activities influence brand awareness, brand image, and brand loyalty for the Netflix brand. This study uses primary data collected through a questionnaire research instrument. The sample in this research is 500 respondents who have subscribed or are currently subscribing to Netflix. This research is descriptive and verification in nature. The data in this study used the help of Statistical Product and Service Solution (SPSS) tools, and Structural Equation Modeling – Partial Least Square (SEM-PLS). Data analysis in this study Instrument Test Results stated that the data in this study proved to be valid and reliable. The results of this study prove that: (1) Social Media Marketing influences Brand Awareness positively and significantly, (2) Social Media Marketing influences Brand Image positively and significantly, (3) Social Media Marketing influences Brand Loyalty positively and significantly, (4) Brand awareness positively and significantly influences Brand Image, (5) Brand Awareness positively and significantly influences Brand Loyalty, (6) Brand Image positively and significantly influences Brand Loyalty. These results have implications for future researchers to examine how the influence of social media marketing of a brand influences brand awareness, brand image, and brand loyalty. The findings of this study have implications for brand owners to formulate social media marketing strategies that can influence brand awareness, brand image and brand loyalty.